DRES-10. DRD5 IS A MODULATOR OF GLIOMA SUSCEPTIBILITY TO DRD2 ANTAGONISM BY ONC201. (5th November 2018) - Vijay Prabhu, Varun; Madhukar, Neel; Gilvary, Coryandar; Kline, C Leah B; Tarapore, Rohinton; El-Deiry, Wafik; Doherty, Faye; VanEngelenburg, Alexander; Durrant, Jessica; Benes, Cyril; Oster, Wolfgang; Elemento, Olivier; et al.
Abstract: ONC201 is the first selective antagonist of dopamine receptor D2 (DRD2) and D3 (DRD3) for clinical oncology that has exhibited preliminary clinical activity in high grade gliomas. We investigated DRD2 dysregulation in glioma and its role in ONC201 efficacy. Investigating CRISPR screens across a spectrum of cancer revealed that glioma cell lines had the highest DRD2 gene essentiality scores, indicating that glioma is a tumor type with the most vulnerability to DRD2 antagonism. Investigation of TCGA revealed that DRD2 is highly expressed in glioblastoma relative to other dopamine receptor family members and is associated with a relatively poor clinical prognosis. Tissue microarray analysis confirmed DRD2 overexpression in glioblastoma relative to normal brain. A linear correlation between DRD2 mRNA and ONC201 GI50 was observed among NCI60 glioblastoma cell lines. Similarly, we found a significant concordance between a cell line's sensitivity to ONC201 within the Genomics of Drug Sensitivity in Cancer (GDSC) panel and its DRD2 gene essentiality score. Next, we ranked the relative contribution of each dopamine receptor to ONC201 efficacy using a bioinformatics approach based on a generalized linear model. We found that the strongest negative contributor was DRD2 – where a negative contribution denotes a decreased IC50 value as expression increases. Interestingly, DRD5, a D1-like dopamine receptor that counteracts DRD2 signaling, was measured as having the highest positive score – indicating that low expression of DRD5 was correlated with ONC201 efficacy. DRD5 expression was significantly inversely correlated with ONC201 potency in the NCI60 and GDSC datasets. Furthermore, a missense DRD5 mutation was identified in tumor cells with acquired resistance to ONC201. Resistance could be recapitulated with overexpression of the mutant or wild-type DRD5 gene. In conclusion, DRD2 dysregulation and DRD5 expression predict preclinical ONC201 glioma sensitivity that may be used to identify additional settings for clinical evaluation.